Symbolic violence conversations with Bourdieu - Burawoy, Michael (Duke University Press, 2019)
Michael Burawoy brings Pierre Bourdieu into an extended debate with Marxism by outlining the parallels and divergences between Bourdieu's thought and preeminent Marxist theorists including Gramsci, Fanon, Beauvoir, and Freire.